A randomized controlled trial to evaluate the effect of 2 hoof trimming methods at dry-off on hoof lesion and lameness occurrence in dairy cattle - G. Stoddard; N. Cook; S. Wagner; L. Solano; E. Shepley; G. Cramer (Journal of Dairy Science)
ABSTRACT: Despite hoof trimming (HT) being a recommended procedure for hoof lesion and lameness prevention, there is limited data on the efficacy of different HT methods. Our objective was to compare the effects of HT cows at dry-off with the functional method that uses a little model (LIT) to an adaptation with bigger modeling (BIGM) of the higher load-bearing hoof on the occurrence of new hoof lesions and the risk for lameness in the next lactation. Cows scheduled for their regular HT at dry-off were enrolled weekly from 3 sand-bedded freestall housed herds located in Wisconsin (n = 2) and Minnesota (n = 1). Cows were eligible for enrollment if they did not have hoof horn lesions at their dry-off HT. Cows were allocated to either LIT or BIGM weekly. Locomotion scores were collected on a biweekly basis from 2 herds, once before enrollment and until their subsequent HT or up to 165 DIM. Two trained hoof trimmers collected hoof lesion data either during the cow's scheduled midlactation HT between 100 and 165 DIM or during an HT prompted by identification as a lame cow by farm personnel. Data were analyzed using multivariable logistic regression, with the presence of any hoof lesion as the outcome of interest and multivariable Cox proportional hazards models, with the presence of lameness as the outcome of interest. A total of 1,556 cows were enrolled, with 790 (51%) cows in the LIT treatment and 766 (49%) cows in the BIGM treatment. The average DIM at the cow's next HT was 113 (95% CI: 111–114 DIM). A total of 205 (16.2%) of 1,265 cows were identified with a lesion before 165 DIM. A total of 501 (43%) of 1,167 cows were identified as lame following enrollment. There was no evidence of a difference between the LIT and BIGM groups overall when presence of any hoof lesion was considered as the outcome. The median time to lameness was 193 d for LIT and 203 d for BIGM. For the hazard of lameness outcome there was no evidence of a difference between the LIT and BIGM groups overall. However, for both the presence of any hoof lesion and lameness outcomes, a cow's lactation group modified the effect of BIGM. First-lactation cows trimmed with BIGM had reduced risk of any hoof lesion and specifically reduced risk for hoof horn lesions (risk difference 6.1%, 95% CI: 9.6%–2.5%) and odds 76% (odds ratio 0.24, 95% CI: 0.10%–0.58%). In addition, first-lactation cows and cows with an enrollment locomotion score <3 had a lower hazard of becoming lame in the following lactation if they were allocated to the BIGM treatment, compared with cows trimmed with LIT. In summary, the effect of the BIGM trimming method was modified by factors related to parity and prior lameness status, possibly influenced by bone exostosis on the third phalanx. Therefore, the BIGM HT method should be considered to prevent lameness and hoof lesions when animals are trimmed at their first-lactation dry-off trim.